Arts-based management between actions and conjunctions: Lessons from a systematic bibliometric analysis - Larbi Safaa; Anas Khazi; Dalia Perkumiençe; Vytautas Labanauskas (Administrative Sciences, 2023)
The imperative demands placed on modern business management necessitate the exploration of novel approaches to adapt, innovate, and ensure effectiveness and efficiency. The integration of art into business management aligns with this rationale, indicating a trend towards art's incorporation into various managerial dimensions. As a discipline primarily focused on understanding managerial practices, management science has been investigating the utilization of art in the workplace since the early 2000s. The subject of art in the business environment has garnered various names and significant attention as a major trend. Through bibliometric analysis, we can characterize the evolution of scientific production and map the prevailing ideas in this field. By examining a sample of 69 articles retrieved from the Scopus database, this study lays the foundation for structuring art-based managerial thinking, while acknowledging certain limitations that may guide future research endeavors.
Keywords: 350; arts-based methods; arts-based initiatives; arts-based management; art infusion; art intervention; vosviewer; R studio